Modification of Exemplar-Based Inpainting Algorithm for Mobile Devices With of Patch Offsets - Gevorgyan , Vahan V.; Karapetyan, Gevorg A.; Sarukhanyan, Hakob G. (Mathematical Problems of Computer Science, 2021)
Inpainting (completion) of digital images is the process of filling in an unknown region with information from the known region of the image. Due to rise of mobile technologies, there is demand on usage of inpainting algorithms on mobile devices for applications such as object removal, image restoration, etc. Exemplar-based inpainting is one of the most popular and efficient inpainting algorithms, but, however, it is slow enough for mobile implementation. The intention of this paper is to develop a high performance inpainting algorithm applicable for mobile devices. We introduce a modification of the algorithm using the statistics of similar patch offsets. This approach reduces the computation time at about 10-30 times, which makes the algorithm work interactive even on mobile devices. The paper includes those experiment results and comparison of the developed algorithm with the exemplar-based inpainting algorithm and showed the advantages of our method on various images.